Lipid-Lowering Efficiency and Safety of Alirocumab 300 mg Using a 2-mL Autoinjector Device in Real-World Practice: The MARS Study - Klaus G. Parhofer; Peter Bramlage; Constanze Gries; Cornelia Harder; Christiane Look; W. Dieter Paar; Ursula Rauch-Kröhnert (Drugs - Real World Outcomes)
Abstract Background Alirocumab is a fully human monoclonal antibody to proprotein convertase subtilisin kexin type 9 used for the reduction of low-density lipoprotein cholesterol (LDL-C) in high-risk patients not reaching their LDL-C target. Recently, a 2-mL prefilled autoinjector has been developed to support the monthly 300-mg dosing regimen with a single-injection administration. Methods and Objectives Monthly application of 300 mg AlirRocumab (Praluent®) using the 2-mL SYDNEY Device (MARS) is a non-interventional, open, prospective, multi-center cohort study conducted in Germany between 2021 and 2023 with an observational period of 12 weeks. Patients included had primary hypercholesterolemia (heterozygous familial or non-familial) or mixed dyslipidemia and confirmed vascular disease and other risk factors or confirmed familial heterozygous hypercholesterolemia. Primary objectives were to assess the effectiveness of the 2-mL SYDNEY autoinjector measured by the lipid-lowering effect of alirocumab and to document therapy satisfaction, patient adherence, and persistence. Secondary objectives were to assess safety (adverse events) and tolerability. Results A total of 146 patients were analyzed: 110 (75.3%) patients were proprotein convertase subtilisin kexin type 9 inhibitor naïve and 36 (24.7%) were pre-treated with a proprotein convertase subtilisin kexin type 9 inhibitor. Patient mean age was 65.6 years with a preponderance of male gender (59.6%). At 12 weeks, the LDL-C value had decreased by a median of 59.5 mg/dL (1.5 mmol/L) in naïve patients (median relative decrease: − 52.0%). In the pre-treated group, the LDL-C value remained mainly unchanged (median slight numerical relative increase: 1.6%). Treatment satisfaction was rated similarly in both groups with most patients being satisfied/very satisfied and rating the injection as effective, safe, and easy to handle. Twenty-three adverse events in 13 patients (8.0%) were documented. Three patients experienced one serious adverse event each; for five patients, an adverse drug reaction was observed, although none was serious. The occurrence of adverse events was similar in both groups. Conclusions Alirocumab 300 mg administered with the 2-mL SYDNEY autoinjector was safe and effective in lowering LDL-C after 12 weeks in a routine clinical setting in Germany. The treatment schedule was perceived to be beneficial with excellent device acceptance and satisfaction, potentially increasing patient adherence. Clinical Trial Registration Clinicaltrials.gov: NCT05129241.